On asymptotics of solutions of one Cauchy’s problem - Zernov , A. E. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
We consider the Cauchy problem $(x')^n=at^r+bx+f(t,x,x'), x(0)=0$. We prove the existence of continuously differentiable solutions and study their asymptotic behavior for $t→+0$.